Anthropometric profile and food consumption of elite football players - Goncalves, Livia de Souza [UNESP]; Souza, Elton Bicalho de; Oliveira, Erick Prado de; Burini, Roberto Carlos [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2015)
The football promotes high energy expenditure of athletes, which makes it necessary to proper food intake, providing optimum levels of muscle glycogen and muscle recovery, fundamental to improve performance. The present study aims to assess body composition and dietary intake of professional football players. This is a descriptive study and evaluated anthropometric variables (weight, height, BMI and skinfolds) and food intake (24-hour food recall) one day after the match. The sample consisted of 12 players, aged 23 + 2.1 years, weight 74.5 + 9.9 kg, height 1.80 +/- 0.1 m, BMI 23.4 + 1.2 kg/m2 and fat percentage of 10.8 + 1.5 %. The majority (n = 7) of respondents holds 5 meals a day, and that most of these meals are consumed in the concentration of the club. All athletes had energy and carbohydrate intake below recommended levels (2586 +/- 698 kcal and 4.9 + 1.2 g / kg, respectively), and did not reach the minimum recommended levels of folate, calcium, magnesium, potassium and vitamin B5. We conclude that the athletes had adequate body composition, however food consumption, especially carbohydrate and calorie intake, was performed below the recommended values.
Keywords: Feeding; Energy Expenditure; Body Composition; Athlete